Nurse work environment and quality of care by unit types: A cross-sectional study. Issue 10 (October 2015) - Ma, Chenjuan; Olds, Danielle M.; Dunton, Nancy E.
Abstract Background Nursing unit is the micro-organization in the hospital health care system in which integrated patient care is provided. Nursing units of different types serve patients with distinct care goals, clinical tasks, and social structures and norms. However, empirical evidence is sparse on unit type differences in quality of care and its relation with nurse work environment. Nurse work environment has been found as an important nursing factor predicting nurse and patient outcomes. Objectives To examine the unit type differences in nurse-reported quality of care, and to identify the association between unit work environment and quality of care by unit types. Methods This is a cross-sectional study using nurse survey data (2012) from US hospitals nationwide. The nurse survey collected data on quality of care, nurse work environment, and other work related information from staff nurses working in units of various types. Unit types were systematically classified across hospitals. The unit of analysis was the nursing unit, and the final sample included 7677 units of 14 unit types from 577 hospitals in 49 states in the US. Multilevel regressions were used to assess the relationship between nurse work environment and quality of care across and by unit types. Results On average, units had 58% of the nurses reporting excellent quality of care and 40% of the nurses reporting improved quality of care over the past year. Unit quality of care varied by unit types, from 43% of the nurses in adult medical units to 73% of the nurses in interventional units rating overall quality of care on unit as excellent, and from 35% of the nurses in adult critical care units to 44% of the nurses in adult medical units and medical–surgical combined units reporting improved quality of care. Estimates from regressions indicated that better unit work environments were associated with higher quality of care when controlling various hospital and unit covariates; and this association persisted among units of different types. Conclusions Unit type differences exist in the overall quality of care as well as achievement in improving quality of care. The low rates of nurses reporting improvement in the quality of nursing care to patients suggest that further interventions focusing at the unit-level are needed for achieving high care quality. Findings from our study also suggest that improving nurse work environments can be an effective strategy to improve quality of care.